Porous poly(vinyl alcohol)/sepiolite bone scaffolds: preparation, structure and mechanical properties - CHEN, BIQIONG; Killeen, David; Frydrych, Martin (Elsevier, 2012)
Porous poly(vinyl alcohol) (PVA)/sepiolite nanocomposite scaffolds containing 0-10 wt.% sepiolite were prepared by freeze-drying and thermally crosslinked with poly(arylic acid). The microstructure of the obtained scaffolds was characterised by scanning electron microscopy and micro computer tomography, which showed a ribbon and ladder like interconnected structure. The incorporation of sepiolite increased the mean pore size and porosity of the PVA scaffold as well as the degree of anisotropy due to its fibrous structure. The tensile strength, modulus and energy at break of the PVA solid material that constructed the scaffold were found to improve with additions of sepiolite by up to 104%, 331% and 22% for 6 wt.% clay. Such enhancements were attributed to the strong interactions between the PVA and sepiolite, the good dispersion of sepiolite nanofibres in the matrix and the intrinsic properties of the nanofibres. However, the tensile properties of the PVA scaffold deteriorated in the presence of sepiolite because of the higher porosity, pore size and degree of anisotropy. The PVA/sepiolite nanocomposite scaffold containing 6 wt.% sepiolite was characterized by an interconnected structure, a porosity of 89.5% and a mean pore size of 79 ?m and exhibited a tensile strength of 0.44 MPa and modulus of 14.9 MPa, which demonstrates potential for this type of materials to be further developed as bone scaffolds.
IN_PRESS
Keywords: Bioengineering; Poly(vinyl alcohol); nanocomposite